Speech Perception in Bilateral Hearing Aid Users With Different Grades of Asymmetric Hearing Loss - Hoppe, Ulrich; Hast, Anne; Hocke, Thomas (Frontiers in Neuroscience, 2022)
Hearing loss is associated with decreased speech perception as well as with changes in the auditory pathway. The effects of those changes on binaural speech perception with hearing aids are not yet fully understood. To provide further evidence on the functional changes of the auditory pathway, several speech perception tests (unilateral and bilateral, aided and unaided, in quiet and in noise) were conducted in a population of 370 bilateral hearing aid users covering the entire range of the World Health Organisation’s most recent classification of hearing loss. To characterise the effects of asymmetric hearing thresholds, a generalised linear model was used for regression analysis. The model revealed a detrimental effect of the poorer ears’ thresholds on both the unaided and the aided unilateral word recognition scores that were attained by the better ear. Moreover, aided binaural word recognition (in quiet and in noise) was affected to a degree that cannot be explained on the sole basis of bilateral summation. Thus, this study provides evidence that there is a reorganisation and altered functioning of the afferent and efferent auditory pathways due to asymmetric hearing loss. Consequently, more attention should be paid to provision with a hearing aid as early as possible, and separately for each ear.